Three-dimensional CT angiography of the canine hepatic vasculature - Jeong, Y.C. (Seoul National University, Seoul, Republic of Korea); Lim, C.Y. (Seoul National University, Seoul, Republic of Korea); Oh, S.K. (Seoul National University, Seoul, Republic of Korea); Jung, J.H. (Seoul National University, Seoul, Republic of Korea); Chang, J.H. (Seoul National University, Seoul, Republic of Korea); Yoon, J.H. (Seoul National University, Seoul, Republic of Korea); Choi, M.C. (Seoul National University, Seoul, Republic of Korea), E-mail: mcchoi@snu.ac.kr (Journal of veterinary science (Suwŏn-si, Korea), 2008)
Eight Beagle dogs were anesthetized and were imaged using a single channel helical CT scanner. The contrast medium used in this study was iohexol (300 mg I/ml) and doses were 0.5 ml/kg for a cine scan, 3 ml/kg for an enhanced scan. The flow rate for contrast material administration was 2 ml/sec for all scans. This study was divided into three steps, with unenhanced, cine and enhanced scans. The enhanced scan was subdivided into the arterial phase and the venous phase. All of the enhanced scans were reconstructed in 1 mm intervals and the scans were interpreted by the use of reformatted images, a cross sectional histogram, maximum intensity projection and shaded surface display. For the cine scans, optimal times were a 9-sec delay time post Ⅳ injection in the arterial phase, and an 18-see delay time post Ⅳ injection in the venous phase. A nine-sec delay time was acceptable for the imaging of the canine hepatic arteries by CT angiography. After completion of arterial phase scanning, venous structures of the liver were well visualized as seen on the venous phase.